Development of Information System Management Customer Satisfaction Using the Simple Additive Weighting Method and Website-Based Google Maps API at ISP XYZ - Ahmad Habib; Putra Aditya Nova; Ardy Januantoro (Soegijapranata Catholic University, 2021)
Internet Service Provider XYZ is a service company that provides a variety of Internet service package products, cloud data, communication networks, and complete installations, as well as various local and international TV channel service packages interactively using fiber optic technology. However, over time, problems arose, where many customers complained about the troubleshooter service management provided by the ISP, for example, related to reports of disturbances from customers, the length of time in handling disturbances, the lack of clarity of officers who handled disturbances and so on which led to a decrease in the level of customer satisfaction. To deal with these problems, researchers developed a customer satisfaction management information system by applying the Simple Additive Weighting method supported by a website-based google maps API to solve the problems being faced by ISP XYZ. The results of the system development are expected to facilitate and speed up the handling of problems that are being experienced by customers and with the application of the SAW method can easily find out the level of customer satisfaction at the XYZ ISP.